Determination of the complete nucleotide sequence of a lupine potyvirus isolate from the Czech Republic reveals that it belongs to a new member of the genus Potyvirus - Sarkisova, Tatiana; Petrzik, Karel (Archives of virology, 2011)
The complete nucleotide sequence of the ssRNA genome of a lupine potyvirus (LP) isolate was determined. It comprised 10,113 nucleotides excluding the poly(A) tail. Phylogenetic analysis of CP protein sequences identified pepper veinal mottle virus, narcissus yellow stripe virus, and chili veinal mottle virus as the closest relatives, sharing coat protein amino acid sequence identities of only about 64% with the LP isolate. Thus, LP can be regarded as a member of a newly described potyvirus species, for which the name Lupine mosaic virus (LuMV) is proposed.
Keywords: Lupinus; Czech Republic; Phylogeny; Genome, Viral; fylogeneze; genom virový; nemoci rostlin; Česká republika; Plant Diseases; Potyvirus